ASUHAN KEPERAWATAN ULKUS DIABETES MELITUS : LAPORAN KASUS - rifatunnisa; Nipa, Yohanes; Paschalia, Yustina P. M. (Poltekkes Kemenkes Kupang, 2023)
Background Diabetes is a metabolic disease that has specific signs in the form of hyperglycemia. The main complications of DM in Indonesia are neuropathy (13%-78%), microvascular complications (16%-53%) and diabetic foot ulcer complications (7.3%-24%). Peripheral neuropathy causes loss of sensation in the distal areas of the feet, resulting in a high risk of foot ulcers and even amputation. Cases of Diabetes Mellitus (DM) Ulcers really need attention to prevent further complications in the form of amputation. Data related to the prevalence of diabetes mellitus ulcers in Ende Hospital (2023) explains that there are variations in data on diabetic ulcers. The prevalence of diabetic ulcers in Ende Hospital in 2020 was 50 people, in 2021 it was 45 people and in 2022 it was 21 people. The purpose of this research is to be able to carry out nursing care for clients with a medical diagnosis of diabetes mellitus ulcers. The research method used is a case study. The case study taken from Ende Regional Hospital was 1 client with nursing care for a client with a medical diagnosis of diabetes mellitus ulcer. Results: client found problems with tissue integrity disorders, potential for infection collaboration, acute pain, nutritional deficits and knowledge deficits about diabetes mellitus ulcers and their management. The interventions used are based on SIKI: wound care, pain management, nutritional management, health education. The conclusion is that the problems of impaired tissue integrity, potential collaboration of infection, acute pain and nutritional deficits have not been resolved. Total DFUAS scoring was 64 with 90% necrotic and 10% slough. Suggestions: Clients and families are expected to be able to care for diabetic wounds themselves at home after being taught how to care for wounds so that the wounds remain dry and clean and infection does not occur. Clients are expected to carry out routine health control and be disciplined in implementing a diabetes mellitus diet.